2020
DOI: 10.1016/j.cell.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Host-Viral Infection Maps Reveal Signatures of Severe COVID-19 Patients

Abstract: Viruses are a constant threat to global health as highlighted by the current COVID-19 pandemic. Currently, lack of data underlying how the human host interacts with viruses, including the SARS-CoV-2 virus, limits effective therapeutic intervention. We introduce Viral-Track, a computational method that globally scans unmapped single-cell RNA sequencing (scRNA-seq) data for the presence of viral RNA, enabling transcriptional cell sorting of infected versus bystander cells. We demonstrate the sensitivity and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
547
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 457 publications
(627 citation statements)
references
References 77 publications
47
547
3
1
Order By: Relevance
“…In particular, tissue resident immune populations of the myeloid lineage in the heart, esophagus and lung also collectively express many of the predicted target genes (Supplementary Figure 3B,4). This is particularly interesting given the recent reports that myeloid lineage and epithelial cells are affected in severe SARS-CoV-2 infection cases 19 .…”
Section: Drugs That Reduce Ace-2 Regulate Steroid Signaling and Peptimentioning
confidence: 91%
“…In particular, tissue resident immune populations of the myeloid lineage in the heart, esophagus and lung also collectively express many of the predicted target genes (Supplementary Figure 3B,4). This is particularly interesting given the recent reports that myeloid lineage and epithelial cells are affected in severe SARS-CoV-2 infection cases 19 .…”
Section: Drugs That Reduce Ace-2 Regulate Steroid Signaling and Peptimentioning
confidence: 91%
“…18 Viral-Track, which allows unsupervised detection of viral RNA in single-cell RNA-seq datasets, also found evidence of SARS-COV-2 infection in monocytes/macrophages in severe patients. 19 In addition, viral antigens were also detected in macrophages infiltrated into the alveolar interstitium and cavities of SARS-CoV-2-infected hACE2-expressing mice. 20 Moreover, immunofluorescent double staining showed that IL-6 is primarily produced by infected macrophages.…”
Section: Ade Can Explain Characteristics Of Severe Covid-19mentioning
confidence: 94%
“…Liver scRNA-seq data processing and estimation of the abundance of liver cell type The healthy liver and cirrhotic liver 10X scRNA-seq matrices were downloaded from GSE136103 (13), and the HBV liver 10X scRNA-seq matrix was obtained from Ido Amit Lab (14). The unsupervised clustering and visualization were performed in the Seurat R package v3.1.1 (15).…”
Section: Resultsmentioning
confidence: 99%